HUBUNGAN PENGETAHUAN IBU TENTANG KESEHATAN REPRODUKSI REMAJA DENGAN UPAYA MEMPERSIAPKAN MASA PUBERTAS PADA ANAK DI SD NEGERI 20 PEKANBARU - Rini Hariani Ratih; Sara Herlina; Yusmaharani Yusmaharani (JOMIS (Journal of Midwifery Science), 2020)
Adolescence is a period of rapid growth and development both physically, psychologically and intellectually. The special nature of adolescents has a great sense of curiosity, likes adventure and challenges and tends to dare to bear the risk of his actions without being preceded by careful consideration. Mothers who have a major role and share in the period of seeing the development of their children to be able to undergo puberty, because mothers who pay more attention and follow the development of each of their children. This study uses quantitative research with analytical methods and cross sectional research design, namely research to see the relationship between independent and dependent variables. The purpose of the study is to determine the relationship of maternal knowledge about adolescent reproductive health with efforts to prepare for puberty in children at SD Negeri 20 Pekanbaru. The results of the study are there is a relationship between maternal knowledge about adolescent reproductive health with efforts to prepare for puberty in children in SD Negeri 20 Pekanbaru with a P value = 0.027.